Penentuan Lama Waktu Istirahat Pekerja Berdasarkan Beban Kerja Fisik padaPT. Perkebunan Nusantara 1 PKS Pulau Tiga - Yusnawati Yusnawati; Yusri Nadia; Ilham Syahputra (Universitas Teuku Umar, 2016)
Energy recovery is very important to note during the working process to avoid fatigue. One of the factors that can affect energy recovery is rest time. Workers with heavy workloads require the period and frequency of breaks that are different from workers with a light workload. Workers with heavy workload cederung get tired and thus require longer rest periods and more often. This research was conducted at PT. Perkebunan Nusantara 1 PKS Pulau Tiga in the sorting Fruit Bunch Oil (TBS), as for the purpose of this study was to assess the workload of workers and clarify the workload by comparing the workload standards, determine the length of rest time workers appropriate in the sorting TBS that they can work with optimum conditions so that the quality of the raw material processed is maintained, and determine the level of energy consumption for the workers at the sorting TBS so that they can work with optimum conditions so that the quality of raw materials TBS maintained, and determine the level of energy consumption of the workers at the sorting TBS , Measurement of physical workload is a simple method to determine the length of time off based on the pulse of current workers to work and rest. From the calculation that the workload (CVL), the worker is greater than 30 percent and categorized at a moderate level and to work in a short time and needed repair. The timing of the break based on the workload is determined by physiological approach. Based on the physiological approach, that breaks given by the manufacturer is not sufficient when compared to the workload of workers sorting the fruit, where the optimal long rest periods for these workers is over 73 minutes or as long as 1,2 hours.Keywords: Workload, Physiological, Break Time